Conservation of Natural and Cultural Heritage in Kenya - Deisser, Anne-Marie; Deisser, Anne-Marie (UCL Press, 2016)
In Kenya, cultural and natural heritage has a particular value. This book brings together essays by heritage experts from different backgrounds, including conservation, heritage management, museum studies, archaeology, environment and social sciences, architecture and landscape, geography, philosophy and economics to explore three key themes: the underlying ethics, practices and legal issues of heritage conservation; the exploration of architectural and urban heritage of Nairobi; and the natural heritage, landscapes and sacred sites in relation to local Kenyan communities and tourism. It thus provides an overview of conservation practices in Kenya from 2000 to 2015 and highlights the role of natural and cultural heritage as a key factor of social-economic development, and as a potential instrument for conflict resolution.
English
Keywords: African history; african history; humanities; Cultural heritage; Kenya; Kikuyu people; Mau Mau Uprising; Nairobi